Salivary Gland Like Breast Carcinoma/Adenoid Cystic Carcinoma: Case Report - Turan Acar; Murat Kemal Atahan; Salih Can Çelik; Kürşat Yemez; Gülden Ballı Ülker; Seyran Yiğit; Ercüment Tarcan (European Journal of Breast Health, 2014)

(untitled)
Adenoid cystic carcinoma of the breast constitutes approximately 0.1% of all breast tumors. They can be located in the trachea, bronchus, cervix, lacrimal gland, and skin as well as the breast. Tumors in the breast have better prognoses compared to those in other locations. The diagnosis and treatment planning of this tumor is challenging due to its rare incidence. In this article, we presented a case that was diagnosed with adenoid cystic carcinoma of the breast upon pathology evaluation. A 59-year-old female patient was admitted to our clinic due to a mass in her right breast. Her mammography revealed a 1 cm in diameter mass in the upper outer quadrant of the right breast, which was classified as BIRADS 4C (Breast Imaging Reporting and Data System). On magnetic resonance imaging (MRI) the lesion was also reported as BIRADS 4C. The patient underwent breast conserving surgery (BCS), and the pathology result was reported as adenoid cystic carcinoma of the breast. The patient received chemo-radiotherapy in the postoperative period. Adenoid cystic carcinoma of the breast has been first described in the salivary glands. They can be confused with benign lesions both on physical and radiological examinations. Sentinel lymph node biopsy (SLNB) can be used since axillary metastases are rare. Local recurrence and distant metastases are also very rare. Usually, BCS followed by radiotherapy is adequate to obtain local control. In selected patients with a poor prognosis, chemotherapy and hormonal therapy should be added to the treatment.